PENINGKATAN KOMPETENSI GURU DALAM PROSES BELAJAR MENGAJAR - Setiyawati, Eny Setiyowati; Akhunani, Ana (Early Stage, 2024)
The purpose of this research was to encapsulate the teacher's competence in the teaching and description of the teacher's improved competence in the process of teaching at RA perwanida 2 jogorogo gang. This research uses qualitative discriminating research. With the subject of Ra's head, Teachers and students and on the way to collect data, writer uses method observation, interview, documentation and rockets. As for the analysis., writer uses a qualitative descriptive analysis technique which is a word picture. The result of this research showed that teachers ra perwanida 2 genggong jogorogo is competent and professional in the field.This can be seen from the level of schooling some qualified s-i on education, as a prerequisite teach to the ra / kindergarten.To the learning process teachers ra perwanida 2 genggong jogorogo / is teaching in accordance with expertise in the field, prepare teaching, arrange preparation learning, find the subject in the curriculum and consistent with the objectives in a teaching cocok.sedangkan teachers ra perwanida efforts to increase 2 genggong jogorogo kompetensinya teachers ra like participating in the consultations, follow upgrading courses, the seminar, discussion and use the print or mass media.As for the head teacher ra ra to increase the competency perwanida genggong jogorogo 2 is to supervise supervision and support new ide-ide from teachers